Crank [videorecording (DVD)] - Neveldine, Mark; Taylor, Brian; Statham, Jason, 1967-; Smart, Amy, 1976-; Ramirez, Efren, 1973- (Lionsgate, 2006)
Chev Chelios is a professional assassin working for the West Coast crime syndicate. Chev is planning to quit the crime syndicate so he can spend more time with his girlfriend Eve. But for Chev, things go very bad when he learns he has been injected with a poison called "The Beijing Cocktail" by his rival Verona. The poison will kill Chev if his heart rate drops. Chev has to protect Eve and he sets out to find answers as well as exacting revenge on those who have betrayed him, all before the poison kills him.